(untitled) (Journal of Educational Sciences, 2024)
The development of critical thinking is one of the main requirements of the modern educational process. Various methods and approaches are used in educational institutions to enhance students’ thinking skills. This article focuses on identifying the achievements of students in chemistry lessons by using problem-based learning technology to foster critical thinking. The study involved 9th-grade students from the specialized boarding school named after Nurtas Ondasynov in the city of Turkestan. A total of 49 students participated, divided into experimental and control groups. During the study, the author utilized tests to determine the preliminary and subsequent knowledge levels of the students. The results of the tests were analyzed both qualitatively and quantitatively. To fully reveal the levels of critical thinking, critical thinking indicators were employed. This study aimed to identify the essence of a problem by asking students simple questions and using brainstorming techniques. The final test results demonstrated a significant improvement in students’ achievements. The levels of thinking skills were as follows: formulating conclusions — 78.14%, data collection — 70.3%, analysis and evaluation — 51.2%. These indicators highlight the students’ ability to analyze and evaluate the knowledge they have learned and retained. For other indicators, such as summarizing — 73.14%, providing evidence — 66.6%, and independent work skills — 68.57%, the results also showed significant improvement compared to the preliminary tests. The study revealed the effectiveness of organizing chemistry lessons with the correct use of a model of problem-based learning technology. Key words: technology of PBL, critical thinking, thinking skills, stages of PBL.